Инвестиционный менеджмент: учеб. пособие / под ред. В.В. Мищенко - Мищенко В.В. (Кнорус, 2008)
Экземпляры: Ч/з (20090610) / Инвентарный номер: 94670 / Цена: 230 / Сис.шифр: 65.261я7 / Авт.знак: И 58 / ББК: 65.261я7